Risk factors for viral hepatitis in pulmonary tuberculosis patients undergoing treatment: A systematic review and meta-analysis - Ilham, Ahmad F.; Andini, Salsabila R.; Afladhia, Hanna L.; Rakasiwi, Muhammad ID.; Burhan, Erlina (Narra Sains Indonesia, 2024)
Liver injury in tuberculosis patients, associated with noncompliance with treatment, is further exacerbated by viral hepatitis, which not only directly harms the liver but also increases susceptibility to drug-induced liver injury. The aim of this study was to analyze the associated risk factors for viral hepatitis in tuberculosis patients. This systematic review and meta-analysis adhere to the PRISMA 2020 statement, and the protocol has been registered with PROSPERO (CRD42023477241). Screening and selection of articles were carried out according to predetermined inclusion and exclusion criteria, utilizing four databases: Embase, Medline, Scopus, and ProQuest. Baseline characteristics and patient-related risk factors from each included study were extracted, followed by a meta-analysis of factors that potentially had significance, with the heterogeneities also being analyzed. Of the 21 included studies out of 6,415 identified records, 12 potential risk factors for hepatitis B and 15 for hepatitis C were subjected to meta-analysis. Some key risk factors included for hepatitis B and C were HIV infection (OR: 3.42; 95%CI: 2.19–5.34 and OR: 6.99; 95%CI: 5.09–9.61, respectively), smoking (OR: 1.55; 95%CI: 1.19–2.02 and OR: 3.06; 95%CI: 1.63–5.75, respectively) and alcohol consumption (OR: 2.38; 95%CI: 1.06–5.37 and OR: 4.32; 95%CI: 2.76–6.78, respectively). Furthermore, meta-analysis indicated that other significant risk factors for hepatitis B and/or C include injecting and non-injecting drug use, multiple sexual partners, tattooing, ear-nose piercing, blood transfusion, dental interventions, homelessness, incarceration, living with prisoners, sexually transmitted diseases, and diabetes mellitus. In conclusion, patients with tuberculosis who have risk factors such as smoking, HIV, or alcohol consumption should be screened for hepatitis B and C to prevent liver injury.